About the issue - CHMYR , Olena (University Scientific Notes, 2022)
This issue of the journal is thematic. It is, according to a good tradition that has developed over many years, dedicated to the birthday of Doctor of Economic Sciences, professor, honored worker of science and technology of Ukraine, famous Ukrainian economist, founder of the scientific school of regionalism, and the placement of productive forces Pila Vasyl Ivanovych, who on January 13, 2022 year turned 90 years old.